Pengaruh Promosi Smartphone Samsung Galaxy Terhadap Keputusan Konsumen Membeli di Parafone IT Center Manado - Kadir, Khusairi; Sumayku, Sontje; Kalangi, Johny (JURNAL ADMINISTRASI BISNIS (JAB), 2016)
Abstract. Erafone the IT Center realizes that in order to take a decision, then the promotion is important in influencing the decision-making product purchases. Promotional be a priority in terms of the introduction of a product to make the decision to purchase the product. Considerations for implementing sales promotion pursued by Erafone IT Center to attempt to introduce to consumers in the case relating to the product Smartphone Promotion is one of the factors determining the success of a marketing program. However berkualitasnya a product, if consumers have never heard of and do not believe that the product would be useful for him, then consumers would never buy it. , Purchase decision is an act of consumers to want to buy the product or not. Of the various factors that influence consumers to purchase a product or service, typically consumers always consider quality, price and product already known by the public The aim of this study was to determine the effect of promotion Smartphone Samsung Galaxy Consumer Buying Decision Against Erafone IT Center in Manado. Correlation test was to determine the effect of promotions on purchasing decisions by comparing the count value of the variable promotion Erafone (X) is greater than t table and show that t count is greater than t table so Ho rejected and Ha accepted. Thus it can be concluded that there is a positive influence between promotion of consumer decisions. Keywords: Promotion, Purchase Decision.